Initial testing of VS‐4718, a novel inhibitor of focal adhesion kinase (FAK), against pediatric tumor models by the Pediatric Preclinical Testing Program. Issue 4 (27th October 2016) - Kurmasheva, Raushan T.; Gorlick, Richard; Kolb, E. Anders; Keir, Stephen T.; Maris, John M.; Lock, Richard B.; Carol, Hernan; Kang, Min; Reynolds, C. Patrick; Wu, Jianrong; Houghton, Peter J.; Smith, Malcolm A.
Abstract: VS‐4718, a novel inhibitor of focal adhesion kinase (FAK), was tested against the Pediatric Preclinical Testing Program's (PPTP's) in vitro cell line panel and showed a median relative IC50 of 1.22 μM. VS‐4718 was tested in vivo against the PPTP xenograft models using a dose of 50 mg/kg administered by the oral route twice daily for 21 days. VS‐4718 induced significant differences in an event‐free survival distribution compared with control in 18 of 36 of the evaluable solid tumor xenografts and in 0 of 8 acute lymphoblastic leukemia (ALL) xenografts, but no xenograft lines showed tumor regression. Future plans include further evaluation of the role of FAK inhibition in combination with ABL kinase inhibitors for Ph + ALL.